Effect of Aqueous Hibiscus Sabdariffa on the Histology of the Testes of Male Albino Wistar Rats - Ayara, Charles; Ujah, Williams Oche; Bafai, Favour Joel; Makanjuola, Victor; Enang, Kingsley Bassey; Williams, Queen Uyo; Akafa, Tensaba Andes; Uduak, Peter Ise; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
Medicinal plants contain physiological principles that over the years had been exploited in traditional medicine for the treatment of various ailments. Hibiscus Sabdariffa is not primarily a medicinal plant, but is used as alternative treatment to a wide variety of medical conditions. It is a plant of various psychoactive properties. This study investigated the histological effect of Hibiscus Sabdariffa aqueous solution on the testes of male albino rats. The research used 20 rats weighing 50-100g and were divided into Group A, Group B, Group C, Group D and Group E. Group A was the control group; unexposed to any form of Hibiscus Sabdariffa. Group B were exposed to the extract in a dosage of 0.5ml only in the morning. Group C were exposed to the extract in a dosage of 0.5ml in the morning and afternoon after (6) six hours. Group D were exposed to the extract in a dosage of 0.5ml in the morning, afternoon and by evening after six-hour intervals. Group E were exposed to the extract in an alternating administrative routine. In the end, the rats were sacrificed and the testes were removed and fixed in 10% formal saline solution. The testes were stained with hematoxylin and eosin. Results on the histology show changes to the histology of the testes of the group administered high doses. The results obtained from hormonal profiling shows a series of reduction in the levels of the evaluated hormones at the given dosage. Therefore, Hibiscus Sabdariffa can damage the histology of the testes at given dosage.